Phytochemicals, antimicrobial and antioxidant activities of Mikania micrantha Kunth and Chromolaena odorata (L.) R.M.King & H.Rob. - Hassan, Nafizah (2021)
Mikania micrantha (M. micrantha) and Cromolaena odorta (C. odorata) are an invasive plant that has become a weed pest, grows aggressively, spreads, and displaces other plants in agriculture corps and generally consumed as traditional medicine purposes by local practitioners. This study was conducted with the aim to determine the physical and botany characteristics of both plants, to identify phytochemical in both species and to assess antimicrobial and antioxidant capacity (DPPH, ABTS and FRAP) in hot water, methanolic and petroleum ether extract of M. micrantha and C. odorata leaf and stem. The physical characteristics of both species such as shape, type, arrangement, margin, base, apex, and vein of leaf, and stem were determined based on dendrology characterization and identification. Phytochemical of methanolic and petroleum ether extract obtained from leaf and stem of M. micrantha and C. odorata was analyzed using Gas Chromatography – Mass Spectrometry (GC-MS) for the identification of biochemical components present. Phytochemical analysis of M. micrantha extract by GC-MS revealed the presence of various compounds such as phenol, fatty acid, sesquiterpenes, diterpenes, alkane hydrocarbon and others which have diverse use. All extract from M. micrantha and C. odorata species were evaluated for their antimicrobial activity through disc diffusion method against four microbes (Bacillus subtilis, Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli) and one fungus (Candida albicans). M. Micrantha extract demonstrated minimal inhibition of targeted microbial activity, and some displayed no inhibition at all. As for antifungal activity, C. albicans were resistant to all extract and there was no activity detected. For C. odorata extract, the result displayed no inhibition to slight inhibition activity towards B. subtilis and S. aureus. Meanwhile, all extract did not show any inhibition zone towards P. aeruginosa and E. coli. The screening of antifungal activity towards C. albicans showed that only hot water extract of C. odorata stems have the reaction while the others were inactive. The measurement of Total Phenolic Content (TPC) of hot water, methanolic and petroleum ether extract of M. micrantha and C.odorata leaves and stems was achieved using folin-ciocalteu reagent reveals that hot water extract for M. micrantha leaves and stems had the TPC value 335.5 mg GAE/g and 323.14 mg GAE/g respectively which was found slightly higher (p<0.05) when compared to standard gallic acid reference. On top of that, all TPC value obtained was above average. The DPPH capacity of each extract 5 mg/ml was tested and it is found that hot water extract for C. odorata leaves and methanolic extract for M. micrantha stems have slightly higher scavenging capacity (91.85 μg/ml and 91.46 μg/ml) respectively at p<0.05 as compared to Trolox while ABTS radical were obtained to be higher in hot water extract for both C. odorata leaves (96.88%) and M. micrantha leaves (96.27%). For FRAP activity hot water and methanol extract for both M. mirantha and C. odorata have slightly higher (p<0.05) antioxidant value while the petroleum ether extract for both M. mirantha and C. odorata shows slightly lower value. The results obtained in this study clearly indicate that hot water and methanolic extract for M. micrantha and C. odorata leaves has a significant potential use as natural antioxidant agent and further research should be explored on the utilization of these resource to cure oxidative damage – related disease.